Evaluating Service Quality of Dairy Farmers’ Cooperatives in Supporting Local Milk Producers Amid Declining Productivity - Abel Gandhy; Ambara Purusottama; Teddy Trilaksono (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Given recent productivity declines, this study aims to evaluate the quality of services provided by dairy farmers’ cooperatives to local farmers, who are both cooperative members and the primary milk suppliers, in the context of declining milk productivity. A quantitative approach was employed, focusing on local farmers as key partners and milk suppliers within the livestock business district, a national livestock development model managed by dairy farmers’ cooperatives. Data were collected from 49 respondents, consisting of 29 farmers from Livestock Business District I and 20 farmers from Livestock Business District II. The assessment began with measuring service quality attributes using a structured scale, followed by an Importance–Performance Analysis (IPA). The results indicate that service attributes are distributed across several IPA quadrants, with critical attributes requiring immediate attention, particularly water supply, milk pricing, and communication with cooperative management. In addition, several other service attributes were identified as needing improvement. These findings provide strategic insights for dairy farmers’ cooperatives to enhance key service quality attributes that are essential for improving cooperative performance. Strengthening these attributes is expected to contribute to better service delivery and, ultimately, to increased milk productivity among local farmers, especially those operating within the livestock business district areas.